Rearranjo fluvial como mecanismo de evolução do relevo em escarpas de margem passiva: Serra Geral Catarinense, sul do Brasil - Michael Vinícius de Sordi (2018)
Long-term relief evolution of passive margin escarpments and its vicinities is a major subject on geomorphology and earth surface sciences in general. Although recent advances through nuclide cosmogenic analysis have been made in the past decades there are few parts of the Globe, and it includes Brazil, that remains poorly understood. In central Santa Catarina State, Southern Brazil, Serra do Mar, main Brazilian escarpment was eroded by Itajaí-Açu river as a consequence of headward erosion and Itajaí-Açu headwaters today locates 200 km inland at Serra Geral escarpment. Additionally, Serra Geral escarpment correspond to water divide between three of main fluvial systems of southern Brazil: Itajaí-Açu, Paraná (Iguaçu) and Uruguay. In the present thesis we present results from radar elevation data (SRTM and ALOS-PALSAR) and aerial imagery data (Landsat/aerial imagery fusion), coupled with terrain data and denudation rates derived from 10Be concentrations measured in sand-sized river-born sediment in order to understand Quaternary relief evolution in Serra Geral escarpment. Eight different compartments were mapped and result from differential action of erosion processes over geological substrata of different composition, structure and genesis; different regional base-levels: Itajaí-Açu, Iguaçu (Paraná) and Uruguai. Eight geomorphological units were mapped divided into two compartments: Depressão do ItajaíAçu, where the compartments are the Planalto intermediário no limite entre bacias oceânicas e continentais and the Depressão do Alto Itajaí-Açu; and the Planalto de Santa Catarina, where 6 units were delimited: Planalto do rio Negro; Planalto do rio Canoinhas; Planalto intermediário interior; Planalto do divisor Uruguai/Iguaçu; Planalto de Caçador; Planalto do rio Canoas. Morphostructural influence over erosive process is noticed through the directing of channel migration process, the high density of faults/ fractures and knickpoints, and direction of first order-streams that shows guidance by faults systems well known in Paraná Sedimentary Basin: E-W and N-S. Areas that presented high structural elements density area (knickpoints and lineaments) are coincident with areas of higher intensity of erosion process and show preference for drainage rearrangement process. Still, drainage network is characterized by two shapes of valleys more frequently: i) V shaped profound valleys, without floodplains, where generally river runs over bedrocks and ii) wide-open valleys, with flat bottoms, and great flooded areas. In the studied area valley morphology is a result of structural characteristics of rocks, mainly attitude/fracturing and faults. Therefore, the present study shows the importance of considering litho-structure as controller factor of valley morphology for better understanding morphogenesis and morphodynamics of sedimentary basins edge areas, especially under humid subtropical climate. Reliefs striping is captained by drainage net from river tributaries of: Canoas and Peixe (Uruguai River tributaries) in southwest and Itajaí-Açu, in the east. Yet, we can stablish different denudation levels where, in general: (i) areas belonging to Itajai river hydrographic basin are the most dissected, with higher altimetric amplitude, higher drainage density and lower base level; the profiles are steep and RDE values are elevated; (ii) portions less dissected, with low altimetric amplitude e drainage density e lower base level belong to Iguaçu (Paraná) river hydrographic basin; topographic profiles are smoother and RDE values lower and (iii) areas belonging to Uruguai river hydrographic basin show intermediary dissection, altimetric amplitude and drainage density, as its profiles and RDE values. Along Serra Geral escarpment, drainage features such as elbows, under-fitted valleys, river profiles anomalies and contrast in values evidence rearrangement process, mainly beheading, by ocean-facing tributaries of the ItajaíAçu River conversely to the inland catchments (Iguazu and Uruguay). 10Be derived denudation rates, from 2.8 ± 0.3 to 58.8 ± 8 m/Ma, reinforced such process. While samples from the Caçador and Araucárias Plateaus yield weighted means of 3.1 ± 0.2 m/Ma and 6.5 ± 0.4 m/Ma, respectively, samples from along the escarpment yield a weighted mean of 46.8 ± 3.6 m/Ma, almost 8 times higher. Such significant denudation rate differences are explained by relief characteristics and base-level control. In this way, we conclude that main process of regional relief evolution is headward erosion between the watersheds that, thanks to headward erosion of Itajaí river tributaries, downgrade all the relief and capture areas belonging to inland watersheds Iguazu and Uruguay rivers that also capture areas each other. Finally, regional scale relief evolution during quaternary was controlled by regional and local baselevel interaction, drainage rearrangement process and lithostructure (faults and fractures) as the escarpment moves from E-W. Such process became dominant where Itajaí-Açu broke through Serra do Mar and started to erode Santa Catarinas Plateau.